Malignancies in children and young adults on etanercept: summary of cases from clinical trials and post marketing reports - Hooper, Michele (BioMed Central, 2013)
BACKGROUND: Malignancy risk may be increased in chronic inflammatory conditions that are mediated by tumor necrosis factor (TNF), such as juvenile idiopathic arthritis (JIA), but the role of TNF in human cancer biology is unclear. In response to a 2011 United States Food & Drug Administration requirement of TNF blocker manufacturers, we evaluated reporting rates of all malignancies in patients ≤30 years old who received the TNF blocker etanercept. METHODS: All malignancies in etanercept-exposed patients aged ≤30 years from the Amgen clinical trial database (CTD) and postmarketing global safety database (PMD) were reviewed. PMD reporting rates were generated using exposure information based on commercial sources. Age-specific incidence rates of malignancy for the general US population were generated from the Surveillance Epidemiology and End Results (SEER) database v7.0.9. RESULTS: There were 2 malignancies in the CTD: 1 each in etanercept and placebo/comparator arms (both in patients 18–30 years old). Postmarketing etanercept exposure was 231,404 patient-years (62,379 patient-years in patients 0–17 years; 168,485 patient-years in patients 18–30 years). Reporting rates of malignancy per 100,000 patient-years in the PMD and incidence rates in SEER were 32.0 and 15.9, respectively, for patients 0–17 years and 46.9 and 42.1 for patients 18–30 years old. Reporting rates were higher than SEER incidence rates for Hodgkin lymphoma in the 0-17 years age group. PMD reporting rates per 100,000 patient-years and SEER incidence rates per 100,000 person-years for Hodgkin lymphoma were 9.54 and 0.9, respectively, for patients 0–17 years and 1.8 and 4.2 for patients 18–30 years old. There were ≥5 cases of leukemia, lymphoma, melanoma, thyroid, and cervical cancers. Leukemia, non-Hodgkin lymphoma, melanoma, thyroid cancer, and cervical cancer rates were similar in the PMD and SEER. CONCLUSIONS: Overall PMD malignancy reporting rates in etanercept-treated patients 0–17 years appeared higher than incidence rates in SEER, attributable to rates of Hodgkin lymphoma. Comparison to patients with similar burden of disease cannot be made; JIA, particularly very active disease, may be a risk factor for lymphoma. No increased malignancy reporting rate in the PMD relative to SEER was observed in the young-adult age group.